Budowa przewagi konkurencyjnej regionu na przykładzie Regionalnej Strategii Innowacji dla województwa pomorskiego (RIS-P) - Sekuła, Alicja (The Competitiveness Advantage Creating on the Basis of Regional Innovation Strategy for Pomerania Voivodeship - RIS-P, 2008)
The article shows and discusses main directions of Regional Innovation Strategy for Pomerania Voivodship from the competitiveness advantage creation point of view. Firstly, there are analyses of the meaning of the terms "competitiveness", "competitiveness advantage", "innovation" and their significance in contemporary economy, especially in regional economy. Then, there are analyses of the role of regional innovation strategies that are one of more important tools in the process of innovation creation and which help to increase growth and development of research and development potential and regional competitiveness. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 92-102